Mechanical studies of cadmium sulfide/cadmium telluride (CdS/CdTe) photovoltaic modules - Armijo, Mark Andrew, author; Sampath, Walajabad, advisor; Radford, Donald, committee member; Sites, James, committee member (Colorado State University. Libraries, 2015)
Commercial Cadmium Sulfide (CdS) and Cadmium Telluride (CdTe) photovoltaic modules are typically 24” x 48”. The processing steps include: glass heating, Cadmium Sulfide (CdS) deposition and Cadmium Telluride (CdTe) deposition, Cadmium Chloride (CdCl2) heat treatment, back contact formation and back contact heat-treatment. The main components of the photovoltaic module under consideration in this research are the tempered front glass, an encapsulant (ethylene vinyl acetate (EVA)) interlayer, and the tempered bottom glass. During processing, the front glass loses a certain degree of temper. This results in the reduction of the residual stress within the front glass and ultimately reduces the strength of the module. The residual stress before and after processing was measured. The glass heating reduced the residual stress from 10,000 psi to approximately 2,500 psi. Even with the loss of the residual stress, the modules passed the static load test of 2,400 Pa and survived the hail impact test (1” ice balls at 50 mph). The mechanical behavior of the composite photovoltaic (PV) modules under static mechanical load and hail impact load utilizing mechanics modeling and experimental testing were characterized. The accuracy of the theoretical model is compared to the results of the experimental testing. The results will provide valuable knowledge for the mechanical characteristics of the PV module. This will contribute to the understanding of the effects of temper loss and whether the module exhibits a loss in strength.
Keywords: mechanical behavior; cadmium sulfide/cadmium telluride; photovoltaic modules